Development and Regeneration in the Endocrine Pancreas. (27th December 2012) - Mansouri, Ahmed
Abstract : The pancreas is composed of two compartments that deliver digestive enzymes and endocrine hormones to control the blood sugar level. The endocrine pancreas consists of functional units organized into cell clusters called islets of Langerhans where insulin-producing cells are found in the core and surrounded by glucagon-, somatostatin-, pancreatic polypeptide-, and ghrelin-producing cells. Diabetes is a devastating disease provoked by the depletion or malfunction of insulin-producing beta-cells in the endocrine pancreas. The side effects of diabetes are multiple, including cardiovascular, neuropathological, and kidney diseases. The analyses of transgenic and knockout mice gave major insights into the molecular mechanisms controlling endocrine pancreas genesis. Moreover, the study of animal models of pancreas injury revealed that the pancreas has the propensity to undergo regeneration and opened new avenues to develop novel therapeutic approaches for the treatment of diabetes. Thus, beside self-replication of preexisting insulin-producing cells, several potential cell sources in the adult pancreas were suggested to contribute to beta-cell regeneration, including acinar, intraislet, and duct epithelia. However, regeneration in the adult endocrine pancreas is still under controversial debate.